SYNTHESIS AND MICROBIAL EVALUATION OF SOME NOVEL ETHYL-4-(SUBSTITUTED PHENYL-5-YL)-6-(6-METHOXYNAPTHALEN)-2-OXO-CYCLOHEXA-3-ENE-1-ETHYL CARBOXYLATE DERIVATIVES - B. JADHAV, SATISH; K. VIBHUTE, PRASHANT; N. BHARATE, YOGESH; K. AGHAO, ARVIND (Innovare Journal of Sciences, 2020)
Objective:A series of some novel pharmacological active moleculeEthyl-4-(substituted phenyl-5-yl)-6-(6-methoxynapthalen)-2 oxo-cyclohexa-3-ene- 1-ethyl carboxylate derivatives were synthesized and evaluated in vitro for Antibacterial activity against staphylococcus aureus, Escherichia coli, Salmonella Typhi, Bacillus subtilis and antifungal activity against Aspergillusniger, Aspergillusflavus and Penicilliumchrysogenum,Fusariummoneliforme. Methods: The present research work describes the synthesis of Cyclohexenones by Michael addition. In the present investigation first Chalcones and their derivatives have been synthesized. Chalcones, 3-(6-methoxynaphthalen-1-yl)-1-phenylprop-2-en-1-one(3a-f) were prepared by the Aldol condensation of substituted acetophenone and 6-methoxy-1-napthaldehyde. Base catalyzed condensation of 3-(6-methoxynaphthalen-1-yl)-1-phenyl prop-2-en-1-one (3a-f) with ethyl acetoacetate (4) yields corresponding Ethyl-4-(substituted phenyl-5-yl)-6-(6-methoxynapthalen)-2-oxocyclohexa- 3-ene-1-ethyl carboxylate (5a-f).The newly synthesized compounds were characterized on the basis of elemental analysis, spectroscopic studies viz, FT-IR, 1H NMR and mass. Results: Literature survey reveals that the synthesized pharmacological active molecule i.e. substituted Ethyl-4-(substituted phenyl-5-yl)-6-(6- methoxynapthalen)-2-oxo-cyclohexa-3-ene-1-ethyl carboxylate (5a-f)was not reported. Conclusion:All these newly synthesized compounds were evaluated for their in vitro antimicrobial activity. Most of the compounds showed potent activity.